A facile approach to obtaining PVDF/graphene fibers and the effect of nanoadditive on the structure and properties of nanocomposites. (January 2020) - Sieradzka, Marta; Fryczkowski, Ryszard; Biniaś, Dorota; Biniaś, Włodzimierz; Janicki, Jarosław
Abstract: The key factors in the design of nanocomposites include obtaining a good adhesion between components and homogeneous dispersion of the nanoadditive in the polymer matrix. Direct mixing of graphene with polymers which are then processed by melt compounding method results in strong tendency of nanoadditive to agglomerate. The article presents a new approach to obtaining poly(vinylidene fluoride)/graphene (PVDF/rGO) nanocomposites in the form of fibers. This method is characterized by the use of graphene oxide (GO) dispersed in the plasticizer instead of graphene. The combination of the fibers forming process with simultaneous reduction of GO to rGO allowed the authors to obtain nanocomposites with graphene homogeneously dispersed in the polymer matrix. Moreover, addition of graphene resulted in formation of β-phase in the nanocomposites, which is characteristic for PVDF and responsible for pyroelectric and piezoelectric properties of this polymer. Graphical abstract: Image 1 Highlights: The PVDF fibers preparation processing temperature provided the partial reduction of graphene oxide to graphene. The conditions of nanocomposites preparation allowed to obtain the homogeneous dispersion of the rGO in the polymer matrix. The addition of reduced graphene oxide into PVDF influenced the content of β-phase in the nanocomposites. The increase in take-up velocity during fibers formation causes an increase in the contents of the β-phase. The appropriate processing conditions facilitated obtaining nanocomposite with better mechanical properties than pure PVDF.